Disordered eating behaviors among female undergraduates in Sichuan, China: key associated factors from a province-wide survey - He, Danli; Siau, Ching Sin; Koo, Hui Chin; Cham, Choy Qing; Alavi, Masoumeh; Chong, Agnes Shu Sze; Singh, Harvinder Kaur Gilcharan (Frontiers in Psychology, 2026)
BackgroundFemale undergraduates are at elevated risk for developing eating disorder symptoms. This cross-sectional study examined predictors of three disordered eating behaviors—uncontrolled eating, emotional eating, and cognitive restraint—among Chinese female undergraduates.MethodsA total of 1,727 participants (mean age = 19.73 ± 1.47 years) completed a web-based survey assessing demographics, sociocultural pressures, body dissatisfaction, fatness concern, body image flexibility, and disordered eating behaviors. Binary logistic regression was used to identify predictors.ResultsOver half of the participants reported high levels of disordered eating behaviors. Uncontrolled eating was significantly associated with older age, higher perceived sociocultural pressures, lower body image flexibility, studying at China West Normal University, and fatness concern. Emotional eating was associated with higher perceived sociocultural pressures, body dissatisfaction and fatness concern. Cognitive restraint was associated with higher perceived sociocultural pressures, fatness concern, and body dissatisfaction. Participants who saw themselves as too fat had higher odds of showing emotional eating and cognitive restraint, while those who felt too thin had lower odds of showing cognitive restraint.ConclusionPerceived sociocultural pressures, body dissatisfaction, and weight-related concerns were key predictors of disordered eating behaviors, highlighting the need for multifaceted interventions tailored to these psychological and sociocultural factors.